Pendampingan Business Management Skills dan Literasi Keuangan Dalam Meningkatkan Keunggulan Kompetitif Produsen Kopi Di Desa Pesantren - Setyo Mahanani; Andi Tri Haryono; Eko Mukminto; Evi Dwi Kartikasari; Teguh Widodo Adrianto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This service was carried out with the aim of providing assistance to coffee processing MSME business actors in Pesantren Village in the form of business management skills and strengthening financial literacy in order to achieve competitive advantage. The methods used include observation, focus group discussion (FGD), and training activities. Initial observations generated data about Kopi Catra, a café in Batang Regency that still needs academic support to develop its business and maintain its existence. FGD activities were conducted by means of focused discussions on induction sources based on the alignment of science and understanding of business management skills, understanding and strengthening financial literacy, and trademarks. This activity involved stakeholders including MSME groups, village governments, community leaders and the Agriculture and Food Security Office. The results of the activity showed an increase in participants' understanding of business management, intellectual property protection (trademarks), and financial strategies that can be applied in their businesses.